Customer segmentation using K-means - Mahdee, Nafis; Shourav, Ishrak Rahman; Tabassum, Tasneem; Nur, Eman; Md Amir, Hamza Howlader (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.